2022
DOI: 10.4018/ijagr.297517
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Spatio-Temporal Clustering of the COVID-19 Patterns Using Spatial Statistics

Abstract: An outbreak of the COVID-19 pandemic caused by the SARS CoV 2 has profoundly affected the world. This study aimed to identify the spatio-temporal clustering of COVID-19 patterns using spatial statistics. Local Moran’s I spatial statistic and Moran scatterplot were first used to identify high-high and low-low clusters and low-high and high-low outliers of COVID-19 cases. Getis-Ord’s〖 G〗_i^* statistic was then applied to detect hotspots and coldspots. We finally illustrated the used method by using a dataset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…The results showed that seven hotspots of COVID-19 cases in provinces were detected in areas of high population density in the north-eastern region of Vietnam (Figure 1). Also in Vietnam, the local Moran's I spatial statistic and Moran scatterplot were successfully employed to identify highhigh and low-low clusters and low-high and high-low outliers of COVID-19 cases from a dataset of 10,742 locally transmitted cases in four COVID-19 waves in 63 prefecture-level cities/provinces in Vietnam (16). A Moran's I autocorrelation and spatial cluster analysis for identifying Coronavirus disease COVID-19 using GIS approach was also successfully carried out in Iraq (17).…”
Section: Results and Discussion 31 Roles Of Geographic Information Sy...mentioning
confidence: 99%
“…The results showed that seven hotspots of COVID-19 cases in provinces were detected in areas of high population density in the north-eastern region of Vietnam (Figure 1). Also in Vietnam, the local Moran's I spatial statistic and Moran scatterplot were successfully employed to identify highhigh and low-low clusters and low-high and high-low outliers of COVID-19 cases from a dataset of 10,742 locally transmitted cases in four COVID-19 waves in 63 prefecture-level cities/provinces in Vietnam (16). A Moran's I autocorrelation and spatial cluster analysis for identifying Coronavirus disease COVID-19 using GIS approach was also successfully carried out in Iraq (17).…”
Section: Results and Discussion 31 Roles Of Geographic Information Sy...mentioning
confidence: 99%
“…Hotspot can separate clusters of high values from cluster of low values. It is, therefore, Getis-Ord's G i * statistic was used to identify the counties of high and low numbers of COVID-19 cases (29,30). The form of Getis-Ord's G i * statistic is defined as follows (31):…”
Section: Getis Ord 𝐆 𝐢 * Statistic-based Hotspot Analysismentioning
confidence: 99%
“…Hotspot can separate clusters of high values from cluster of low values. It is, therefore, Getis-Ord's 𝐺 𝑖 * statistic was used to identify the counties of high and low numbers of COVID-19 cases (45,46). The form of Getis-Ord's 𝐺 𝑖 * statistic is defined as follows (47):…”
Section: Hotspot Analysismentioning
confidence: 99%
“…The Getis-Ord's 𝐺 𝑖 * coefficient at county i (𝐺 𝑖 * ) also ranges between -1 and +1. If 𝐺 𝑖 * > 0 and p(𝐺 𝑖 * ) < α then there exists a spatial clustering of high-high values (45,46). In this case, these high-high values, so-called a hotspot, reflects the presence of high numbers of COVID-19 cases among county i and its neighborhood counties (𝑗 ∈ 𝐽 𝑖 ).…”
Section: Hotspot Analysismentioning
confidence: 99%
See 1 more Smart Citation